Modelling consumer’s intention to use IoT devices: role of technophilia - Nusrat Jahan; Md. Abu Hosen Shawon; Farzana Sadia; Dilara Khanom Nitu; Md. Enam Kobir Ribon; Imran Mahmud (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The present study has been conducted to examine whether skills and general technology-related value (GTV) required to operate the internet of things (IoT). This study also investigates is there any effect of technophilia to adopt IoT. The research method we use in this quantitative study was the sample survey. For investigating results, 352 surveys were conducted where 26 surveys were led through online and 292 surveys were distributed to different age groups. The proposed model was examined using partial least square structural equation model where the results revealed that IoT skills and General knowledge on technology directly contribute to technophilia which covers behavioural, emotional, and cognitive aspects. That is if people have a fascination for new technologies then they are willing to use IoT.